Pengaruh experiental marketing terhadap revisit intention dengan kepuasan sebagai variabel mediasi pada pengunjung Taman Rekreasi Selecta - Hendrawan Aditya; Monika Tiarawati (Peneliti.net, 2023)
Tourism is designated as the leading sector for Indonesia's economic development. The tourism sector continues to develop its potential in the hope of increasing tourist visits. Tourism development can be done by changing facilities to attract the attention of tourists. Various changes to existing facilities are expected to be able to provide a positive experience from visitors so as to create satisfaction and intention to visit again. The purpose of this study is to analyze and discuss the effect of experiential marketing on revisit intention with satisfaction as a mediating variable for visitors to Selecta Recreational Park.This study uses the characteristics of respondents with an age range of 19-50 years with the condition of visiting Selecta Recreation Park in 2021 to 2023. The number of samples used in this study was 210 respondents. The type of research used is quantitative.The results of the study show that experiential marketing has a positive and significant effect on satisfaction, satisfaction has a positive and significant effect on revisit intention, and experiential marketing has a positive and significant effect on revisit intention by mediating satisfaction partially proven..